Skills and occupational attainment : a comparative study of Germany, Denmark, and the UK - Dieckhoff, Martina [Verfasser] (My University, 2008)
"This article investigates the impact of vocational education and training on labour market outcomes In Germany, Denmark, and the UK. Using the European Community Household Panel the article analyses how workers with vocational training fare in comparison to both their untrained counterparts and those with higher levels of general education. Three outcomes are examined: wages, the odds of being in a lower-skilled job, and the odds of being in professional employment. The results show that returns to vocational training differ markedly across the three countries studied." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Qualifikationsverwertung; Berufseinmündung; Zweite Schwelle; Bildungsniveau; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Großbritannien